Data analysis in space physics: My experience and lessons learned - Kronberg, Elena A. (Frontiers in Astronomy and Space Sciences, 2022)
The specific area of investigation focused on in this perspective is data analysis in space physics. This paper is intended to be useful for those who start working with observations in space physics, especially with a focus on charged particle measurements. I forward lessons I learned regarding the data analysis such as calibration, statistics and machine learning. I also list practices which I find important in research in general. An outlook on possible future directions in space physics is given.